Use of standardized letters of recommendation for orthopaedic surgery residency: a national survey study. Issue 1 (17th January 2023) - Samade, Richard; Kogan, Monica; Porter, Scott E.; Patt, Joshua C.; Samora, Julie B.
Abstract : Background: Standardized letters of recommendation (SLORs) were introduced to facilitate the comparison of applicants for orthopaedic surgery residency positions, but concerns have arisen regarding the prevalence of their use and potential limitations. Methods: An 11-question electronic survey was sent to all letter of recommendation (LOR) authors and program coordinators who were identified as having completed or prepared a SLOR during the 2020 orthopaedic surgery residency match cycle. A total of 740 LOR authors and 218 program coordinators were invited via initial and reminder electronic mail messages. Results: The survey response rate was 18.1% for LOR authors and 25.2% for program coordinators. The proportion of LORs written that were SLORs significantly increased from prior to the 2020 match cycle to the 2020 match cycle (72.7% to 90.2%, ratio =1.240, P <0.001). There was not a significant increase in the proportion of LORs that were SLORs prepared by program coordinators (83.7% to 77.6%, ratio =0.927, P =0.375). A majority of LOR authors and program coordinators were aware of electronic (82.1% and 76.5%, respectively) and paper SLORs (91.0% and 88.2%, respectively). Conclusions: This study found that SLOR usage increased among LOR authors. However, a parallel increase in SLOR preparation was not reported by program coordinators. Level of Evidence: Level III